Incentives and group identity - Paolo Masella; Stephan Meier; Philipp Zahn (Institute for the Study of Labor (IZA), 2012)
This paper investigates in a principal-agent environment whether and how group membership influences the effectiveness of incentives and when incentives can have hidden costs, i.e., a detrimental effect. We show experimentally that in all interactions control mechanisms can have hidden costs for reasons specific to group membership. In within-group interactions control has detrimental effects because the agent does not expect to be controlled and reacts negatively when being controlled. In between-group interactions, agents perceive control more hostile once we condition on their beliefs about principal's behavior. Our finding contributes to the micro-foundation of psychological effects of incentives.
Keywords: C91; D03; Z13; 330; social identity; social preferences; incentives; motivation; crowding out; trust; experiment